고기구이에서 발생하는 대기오염물질의 배출 특성 - 박성규(Park, Seong Kyu); 김대근(Kim, Dae kuen); 황의현(Hwang, Ui Hyun); 이정주(Lee, Jeong Joo); 이준복(Lee, Jun bok); 배일상(Bae, Il Sang); 어수미(Eo, Soo-mi); 정권(Jung, Kweon) (한국기후변화학회지, 2015)
Emission characteristics from charbroiling of four different meats (beef, port, duck and chicken) in a pilot-scale cooking facility were investigated in this study. The analyzed air pollutants include gaseous species (CO, NO, SO2, NH3 and PAHs) as well as particulate matters (TSP, PM10, PM2.5 and black carbon). The emission factors of PM10 and PAHs were in the range of 3∼47 g-PM/kg-meat and 0.6∼11.41 mg-PAHs/kg-meat, respectively, depending on the type of a meat. In addition, the results also revealed that the high ratio of PM2.5 to TSP in a meat charbroiling should be considered to design and to operate air pollution control devices. KCI Citation Count: 2